Laços e amarras das relações conjugais: pesquisa qualitativa sobre a excessiva dependência feminina dos vínculos conjugais - Bertaglia, Patricia Cristina De Conti (2012)
The present work aims at understanding the psychic contents involved in the excessive woman dependence of the matrimonial bonds, to analyse the fancies on these bonds and to find out archetypical grounds of the identified fancies, taking into account the analytic psicolology point of view and its followers. For the development of the research it was employed the qualitative method, with semi-directed individual interviews and draws. Three married women, 30 to 45 years-old who presented conflicts between desire of remaining married and desire of matrimonial separation, charaterized by emotional suffering and excessive affective dependence of their matrimonial bonds have been interviewed. The results of the research indicate that the feminine excessive dependence of the matrimonial bonds can be relied on self-image problems and troubles to deal on limits, as well as on parental complexes, on romantic fancies and matrimonial idealizations, which neglect the deepest subjectiveness of these women. On the analysis and discussion it was utilized the enlargement by the myths of Hera, Eros and Psyque, Narcise and Eco